REFORMAS DEL ART. 5 LITERAL B DE LA LEY ORGÁNICA DE DONACIÓN Y TRASPLANTES DE ÓRGANOS, TEJIDOS Y CÉLULAS; EN LO RELACIONADO A LA EXPRESIÓN DE VOLUNTAD DE LAS PERSONAS Y DONANTES - Jumbo Tibi, Luis Eduardo (2016)
The present investigative work tries on the donation of organs at national level with the purpose of summarizing the biggest quantity in information on the donation, transplant of organs, fabrics and cells; whose objective is to give to know all the antecedents that it embraces this topic, to provide a lawful solution to the outlined problem. The Organic Law of Donation and Transplants of Organs, Fabrics and Cells in Equator were approved March 04 the 2011 and he/she entered later in validity one year. It is necessary to point out that this Law establishes the presumed will to inform to the citizenship all envelope the related to the donation and transplant whose choice should only be taken by the donor, giving him/her to know its rights and responsibilities that this Law demands. Once setting in validity the Organic Law of Donation and Transplants of Organs, Fabrics and Cells, it should be undertaken a diffusion campaign and concientization of the importance of transforming all the citizens into donors to save lives, but before the lack of information of the present Law, it continues there being resistance to donate the organs, fabrics and the deceased's cells; on the part of the relatives that have lost a to be wanted who you/they block the execution of the lawful existent norm, transforming this into a lawful latent problem, for the execution of the donation. For that exposed previously, when not having an explanation and alternative lawful to the relatives of people that are in terminal stage, private of the freedom, with discapacited and of the third age; who they will choose if they want to be or not donors of organs, fabrics and cells. It is hence that the present investigation will be focused in carrying out the reformations of the art. 5 literal b, 29, 30 and 31 of the Organic Law of Donation and Transplants of Organs, Fabrics and Cells.